On the irregular variations in the light curves of RY Vul - Udovichenko, S. N.; Keir, L. E. (Одеські астрономічні публікації, 2018)
The star RY Vul according General Catalogue of Variable Star (GCVS) is RR Lyr variable, but period and initial epoch are unknown. To determine these parameters the photometric observations during several seasons in 201 1-201 7 of the variable star RY Vul on the Astronomical station near Odessa have been carried out . The 48-cm telescope reector AZT-3 equipped with CCD photometer was used. The light curves in V and R band were obtained and analyzed. It turned out that the light curves of the star is fully irregular. Therefore, the variable star RY Vul should be attribute to type " irregular variables " .